Flexibility Level of Elderly Community Participating in Gymnastics in Banjarbaru City - Badali akbar; Mita Erliana; Recky Ahmad Haffyandi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The purpose of this study was to determine the level of flexibility of the elderly community who participated in gymnastics in the city of Banjarbaru. This study used a quantitative descriptive method with a chair sit and reach test.ui measurement test of the flexibility of the elderly in the city of Banjarbaru. The population was 30 people and the sample was 16 elderly people with a sampling technique using purposive sampling (willingness to be a research sample and age limits). The results of the study showed that the level of flexibility of the elderly community who participated in gymnastics in the city of Banjarbaru was in the very good category (25%), in the good category (12.5%), in the sufficient category (6.25%), in the less category (6.25%), in the very less category (50%). The conclusion of the results of the study showed that the level of flexibility of the elderly community who participated in gymnastics in the city of Banjarbaru was in the very less category.